The Economy of Open and Distance Learning: Evidence from Literature Review - Ngoboka, Mkanibwa; Ndawi, Joseph; Ndekwa, Alberto Gabriel (IJRDO- Journal of Educational Research, 2017)
This paper focused on analyzing the significant contribution of Open and Distance learning ininclusive growth education and its economy in general. Data collection was based ondocumentary review of 15 empirical studies in Africa and worldwide. Content analysis was usedin analyzing data collected from prior empirical studies. Finding using content analysis hasindicated that open and distance learning offer inclusive growth education to disadvantagepopulation. In additional, financial saving, education services, poverty reduction, time saving andwomen empowerment where identified as an economy played by open and distance education.The study recommended that the Nation education scheme of any developing countries should beenforced and encouraged to facilitate open and distance system in order to boost social economicdevelopment and include the disadvantage population in higher education system.